Web 2.0 The Business Model - Lytras, Miltiadis D.; Damiani, Ernesto; Ordóñez de Pablos, Patricia (Springer US : Imprint: Springer, 2009)
Web 2.0 is one of the most prominent business models for information systems available today. It brings together technology and social networks, and the interactivity that creates business value. Web 2.0: The Business Model, an edited volume, is the first reference that integrates the business implications of Web 2.0/3.0, along with its linkage to business. The Editors' discussions emphasize three major components of Web 2.0: social networks analysis, recommendation systems and community building. This volume also includes a number of successful business models for business exploitation using Web 2.0 and Web 3.0 with various case studies. Web 2.0: The Business Model is designed for professionals working as policy makers, corporate quality managers, and government officers in IT, as well as for researchers, professors and advance-level students in computer science and business management.